Análise da viabilidade econômica da geração de energia elétrica a partir do biogás de suinocultura em terminação - Alves, Rodrigo Baduco (2019)
The viability of biogas production and electric power generation for small pig farms is different according to the installed herd. The herd of 1000 and 2000 pigs were selected, where two factors were applied for the production of biogas per animal head, with 0.12 m³ of animal biogas per day and 0.16 m³ of biogas per animal, presenting 4 different scenarios , scenario 1 – 1000 pigs with a biogas production factor of 0.12 m³, scenario 2 – 1000 pigs with a biogas production factor of 0.16 m³, scenario 3 – 2000 pigs with a biogas production factor of 0.12 m³ and finally scenario 4 – 2000 pigs with a biogas production factor of 0.16 m³ per head. After this determination, the biodigestion system and electric energy generation of the 4 scenarios were identified for CAPEX identification, OPEX and the kWh value was R $ 0.36. Assuming that the producer will consume all the electric energy generated, the cash flow with the inflow of revenues and expenses was elaborated in a period of 20 years to identify when the project would be paid, what the attractiveness was and if it would be feasible economic development. Scenario 4 was the one that presented better viability with the discounted payback of 6.3 years, followed by scenario 3 with discounted payback of 8.5 years, scenario 2 only shows viability when analyzed in the long term, since the payback was 16.1 years and scenario 1 did not present economic viability in the period of 20 years. It is important to note that for the feasibility of the project only the generation of electric energy was considered, the use of biofertilizer and the environmental value with the correct treatment of the effluent through the biodigestion system were not included in the study.